Предмет: Математика,
автор: druzhchenko200
sin(a+b)cos(a-b)=sina cosa+sinb cosb
Докажите тождество
Ответы
Автор ответа:
0
sin(a+b) = sina*cosb + cosa*sinb
cos(a - b) = cosa*cosb+sina*sinb
sin(a+b)*cos(a-b) = sina*cosa*(cosb)^2 + sinb*cosb*(cosa)^2+sinb*cosb*(sina)^2 + sina*cosa*(sinb)^2 = sina*cosa*((sinb)^2 + (cosb)^2) + sinb*cosb*((sina)^2 + (cosa)^2) = sina*cosa + sinb*cosb - что и требовалось доказать
cos(a - b) = cosa*cosb+sina*sinb
sin(a+b)*cos(a-b) = sina*cosa*(cosb)^2 + sinb*cosb*(cosa)^2+sinb*cosb*(sina)^2 + sina*cosa*(sinb)^2 = sina*cosa*((sinb)^2 + (cosb)^2) + sinb*cosb*((sina)^2 + (cosa)^2) = sina*cosa + sinb*cosb - что и требовалось доказать
Похожие вопросы
Предмет: Математика,
автор: svlvvaleria
Предмет: Биология,
автор: Аноним
Предмет: Математика,
автор: bazarovaojsanam
Предмет: Математика,
автор: golyshev05
Предмет: География,
автор: karinayo23445